2018
DOI: 10.1016/j.celrep.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Regulatory Logic of the Drosophila Male Stem Cell System

Abstract: The niche critically controls stem cell behavior, but its regulatory input at the whole-genome level is poorly understood. We elucidated transcriptional programs of the somatic and germline lineages in the Drosophila testis and genome-wide binding profiles of Zfh-1 and Abd-A expressed in somatic support cells and crucial for fate acquisition of both cell lineages. We identified key roles of nucleoporins and V-ATPase proton pumps and demonstrate their importance in controlling germline development from the supp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 79 publications
2
11
0
Order By: Relevance
“…In a previous study we identified nucleoporins as important regulators of cyst cell function and cyst cell-germline coordination (Tamirisa et al, 2018). In this study, we go one step further and highlight the critical function of three new nucleoporins in Drosophila testis cyst cells, the central channel FG-rich Nup62, the cytoplasmic ring proteins Nup214 and Nup88, and of the unique Drosophila Exportin encoded by the embargoed (emb) gene.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In a previous study we identified nucleoporins as important regulators of cyst cell function and cyst cell-germline coordination (Tamirisa et al, 2018). In this study, we go one step further and highlight the critical function of three new nucleoporins in Drosophila testis cyst cells, the central channel FG-rich Nup62, the cytoplasmic ring proteins Nup214 and Nup88, and of the unique Drosophila Exportin encoded by the embargoed (emb) gene.…”
Section: Introductionmentioning
confidence: 78%
“…Loss of Nup98-96 leads to dramatic cell autonomous effects in Drosophila male germ cells, since germ cells differentiate prematurely to spermatocytes at the 2-, 4-, and 8-germ cell cysts stage (Parrott et al, 2011). Moreover, loss of nup205, nup93-1, nup358, nup44A in Drosophila testis cyst cells leads to an overproliferation of early germ cells (Tamirisa et al, 2018). Finally, LamDm0 acts downstream of the EGFR pathway and together with the nuclear basket Nup153 and Mtor regulate nuclear retention of the phosphorylated MAPK dpERK (Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selectivity of expression of Dam:PolII or Dam avoids the requirement for cell isolation prior to genomic DNA extraction. Previous applications of TaDa in Drosophila have profiled relatively abundant cell populations in central brain tissue, the intestine or the male germline 14, [17][18][19] . Although OSN classes can be effectively labeled using transgenes containing promoters for the corresponding receptor genes, it was unclear whether TaDa would be sufficiently sensitive to measure transcriptional activity from an individual population of sensory neurons within the antenna.…”
mentioning
confidence: 99%